Кваліфікація лікарських (медичних) помилок - Скриннікова, К. О.; Skrynnikova, K. O.; Катерина Скриннікова (Науковий вісник Ужгородського національного університету. Серія : Право. - 2023. - Вип. 80, т. 1. - С. 239-245, 2023)
У статті проаналізовано класифікацію лікарських помилок за причинами, зокрема: діагностичні помилки; лікувально-тактичні помилки; технічні помилки; організаційні помилки та деонтологічні помилки. Надана правова оцінка лікарської (медичної) помилки як однієї з можливих підстав цивільно-правової відповідальності. Обґрунтовано, що відповідальність лікаря, медичного персоналу залежить від наявності вини в його діях і кваліфікації негативного результату надання медичної допомоги. Підкреслено, що лікарі (медичні працівники) несуть відповідальність не за лікарську помилку, а саме за шкоду, заподіяну пацієнту внаслідок цієї помилки. Сформульовано науково обґрунтовані пропозиції та рекомендації щодо удосконалення цивільного законодавства України у сфері медицини.

In the article the author investigates the qualification signs of actions (inaction) of doctors (medical staff), the consequence of which is a medical error. Their content and influence at the civil law relations that arise between the doctor and the patient are established. The author emphasizes the development of a correct, well-thought-out and unified position about the legal qualification of erroneous actions of doctors (medical staff). Also in the article it is noted that possible defects of medical care are: lack of a positive result, accident, medical error, where medical error is the basis for bringing to civil liability for doctors (medical workers). It is noted that the characteristic signs of such an error are harm to the patient`s health or his death and the presence of both intentional guilt and negligence and wrongful acts (inaction) of doctors (medical workers). The analysis and classification of the causes (factors) of occurrence and types of medical error is carried out. The subjective and objective reasons influencing actions (inaction of doctors, medical workers are defined). It is said that the objective reasons the doctor, the medical worker cannot predict and which exclude their responsibility. It is stated that actions under the influence of objective reasons should be considered as types of accident (or incident). Subjective causes (factors) are errors made by doctors (health professionals) that unreasonably deviate from established medical standards, act carelessly, confidently or allow unreasonable risks in the absence of experience or knowledge. The article analyses the classification of medical errors by the causes, in particular: diagnostic errors; medical and tactical errors; technical errors; organizational errors and deontological errors. A legal assessment of a medical error as one of the possible grounds for civil liability is provided. It is substantiated that the responsibility of a doctor, medical staff depends on the presence of guilt in his actions and the qualification of the negative result of medical care. The article also emphasizes that doctors (medical workers) are not responsible for a medical error, but for the damage caused to the patient as a result of this error. Scientifically substantiated proposals and recommendations for improving the civil legislation of Ukraine in the field of medicine are formulated.

В статье проанализирована классификация врачебных ошибок по причинам, в частности: диагностические ошибки; лечебно-тактические ошибки; технические ошибки; организационные ошибки и деонтологические ошибки. Дана правовая оценка врачебной (медицинской) ошибки как одного из возможных оснований гражданско-правовой ответственности. Обосновано, что ответственность врача, медицинского персонала зависит от наличия вины в его действиях и квалификации негативного результата медицинской помощи. Подчеркнуто, что врачи (медицинские работники) несут ответственность не за врачебную ошибку, а именно за ущерб, причиненный пациенту в результате этой ошибки.
Qualification of medical (medical) errors
Keywords: лікарська помилка; помилка; шкода; кваліфікація; відповідальність; медичні працівники; лікарі; пацієнт; medical error; error; harm; qualification; responsibility; medical workers; doctors; patient; врачебная ошибка; ошибка; вред; квалификация; ответственность; медицинские работники; врачи; пациент